Pharmacokinetics of [14C]teicoplanin in male rats after single intravenous dose. - Bernareggi, A (1986)
The pharmacokinetic profile of [14C]teicoplanin was studied in male Sprague-Dawley rats given a single 10,000-U/kg intravenous dose. The disposition of the antimicrobial activity in the body was estimated by a three-compartment open model. Plasma concentration data were fitted to a three-exponent equation. The profile of total 14C in plasma was similar to that of the microbiological activity. The cumulative recovery of total 14C 5 days after drug administration averaged 76.3% of the administered dose in the urine and 8.7% in the feces. The residual dose remaining in the animal carcasses was 11.1%. Teicoplanin was widely distributed in the body. In almost all organs, the maximum concentration of [14C]teicoplanin was already reached at the first time of killing, which was 0.25 h after the administration of drug. The liver, kidneys, skin, and fat contained most of the residual dose found in the animal carcasses 120 h after administration and behaved as a deep compartment with the adrenal glands and spleen.